Pengaruh Suhu Reaksi Pada Proses Hidrasi Alpha Pinene Dengan Katalisator Amberlyst 36 - Norma Eralita; Ayu Pramita; Dini Nur Fauziah (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
ndonesian turpentine contains 65-85% α-pinene, 1% camphene, 1-3% β-pinene, 10-18% 3-carene and 1-3% limonene. The largest content of turpentine is alpha pinene. Alpha pinene is also a monoterpene compound that has double bonds and is the main raw material in the perfume industry. In addition, alpha pinene is also an important raw material for the manufacture of fine chemicals that have high sales value such as pine oil, camphor and alpha terpineol. To increase the sale value, alpha pinene can be further processed into derivative compounds such as alpha terpineol and alpha terpinyl acetate. Both are valuable derivative compounds used in the perfume industry and the pharmaceutical industry. Hydration is the reaction between alpha pinene and water to produce alpha terpineol compounds. In the reaction process that will be carried out on alpha pinene usually uses a catalyst that can accelerate the reaction rate without becoming a byproduct, catalyst used in this study is a type of resin. This study aims to study the effect of temperature variables at temperatures of 65, 75, 85 and 950C. The conversion of alpha pinene increases with increasing reaction temperature. Assuming a reversible reaction, the relationship of temperature to each reaction rate constant is determined according to the Arrhenius equation.